Formation Of Students' Pragmatic Competence in Mother Language Classes on The Basis of the "4k" Model - Olloqova Oʻgʻiljon Mamanazarovna (Zien Journals, 2023)
The article talks about the new generation textbooks created on the basis of the "4K" model, their importance in the comprehensive development of students. The formation of pragmatic competence in students through teaching based on the communicative principle of the "4K" model is described. Some exercises aimed at the formation of pragmatic competence in students in the primary-grade native language textbook have been analyzed
Keywords: 4K; model; principle; critical